Project-Based Learning as an Effective Pedagogical Intervention for Slow Learners in Elementary Science Education - Nasaruddin Nasaruddin; Mumpuniarti Mumpuniarti (Papanda Publisher, 2026)
Slow learner students face significant challenges in science education due to cognitive processing difficulties and abstract concept comprehension limitations. This study investigated the effectiveness of Project-Based Learning (PjBL) in improving IPAS learning outcomes among slow learner students in elementary education. Employing Classroom Action Research following the Kemmis and McTaggart spiral model, the study was conducted across two iterative cycles with two sixth-grade slow learner students at SD Negeri 012 Sandaran during the 2024/2025 academic year. Data collection utilized mixed methods including pre-tests, post-tests, project assessment rubrics, structured observations, interviews, and documentation. Students engaged in hands-on environmental projects related to